2015
DOI: 10.1093/europace/euv018
|View full text |Cite
|
Sign up to set email alerts
|

Depressed mood amplifies heart-related symptoms in persistent and paroxysmal atrial fibrillation patients: a longitudinal analysis—data from the German Competence Network on Atrial Fibrillation

Abstract: Depressed mood is associated with AF symptom burden over 6 months after adjustment for perceived frequency and duration of AF episodes, COPD, and sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 19 publications
5
34
1
2
Order By: Relevance
“…U pacjentów z AF często stwierdza się zmiany w istocie białej mózgu, zaburzenia czynności poznawczych [28][29][30], pogorszenie jakości życia [31,32] oraz obniżony nastrój [33], a każdego roku jest hospitalizowanych 10-40% pacjentów z AF [23,34,35]. Bezpośrednie koszty AF stanowią już w przybliżeniu 1% wszystkich wydatków na opiekę zdrowotną w Wielkiej Brytanii, a w Stanach Zjednoczonych w 2008 roku wyniosły 6-26 mld dolarów [36,37], co wynika z powikłań związanych z AF (np.…”
Section: Zgonunclassified
“…U pacjentów z AF często stwierdza się zmiany w istocie białej mózgu, zaburzenia czynności poznawczych [28][29][30], pogorszenie jakości życia [31,32] oraz obniżony nastrój [33], a każdego roku jest hospitalizowanych 10-40% pacjentów z AF [23,34,35]. Bezpośrednie koszty AF stanowią już w przybliżeniu 1% wszystkich wydatków na opiekę zdrowotną w Wielkiej Brytanii, a w Stanach Zjednoczonych w 2008 roku wyniosły 6-26 mld dolarów [36,37], co wynika z powikłań związanych z AF (np.…”
Section: Zgonunclassified
“…Symptoms of depression and/or anxiety are associated with greater symptom severity of AF (810), and with recurrence of AF (7). Furthermore, depressive mood has been shown to be more common among patients with persistent AF than paroxysmal AF (11).…”
Section: Introductionmentioning
confidence: 99%
“…The association between psychosocial factors and CVDs has long been recognized, and a recent meta-analysis of prospective epidemiological studies found that psychological factors predict cardiovascular morbidity and mortality [ 1 , 2 ]. Specifically, depression has been associated with coronary heart disease (CHD) [ 3 , 4 ], and with atrial fibrillation [ 5 , 6 ]. After acute coronary syndrome (ACS), depression is a risk factor for all cause and cardiac mortality, as well as for composite outcomes including mortality or non-fatal cardiac events [ 7 ].…”
Section: Introductionmentioning
confidence: 99%